Hukum Jual Beli Anjing untuk Berburu Perspektif Mazhab Hanafi dan Mazhab Syafi'i (Studi Kasus di Nagari Balai Baiak) - Muhammad Riko; Ramadhan Syahmedi Siregar (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstracts: This study aims to analyze the law of buying and selling hunting dogs from the perspective of the Hanafi and Shafi'i schools of Islamic jurisprudence, with a case study in Balai Baiak Village. In Balai Baiak, the tradition of hunting wild boars (